LENGTH WEIGHT RELATIONSHIP AND REPRODUCTION OF WAULANG FISH (Priacanthus hamrur) IN THE WATERS OF BANDA, MALUKU - Ima, Tjameria La; Yusuf, Ruliati; Riska, Riska; Tuapetel, Friesland (Jurnal Perikanan Unram, 2025)
The waters of Banda Neira in Central Maluku are known for their high marine biodiversity, including the waulang fish (Priacanthus hamrur), which holds both ecological and economic value. This study aimed to examine the length–weight relationship, gonadal maturity stages, and gonadosomatic index (GSI) as a basis for sustainable fisheries management. The research was conducted from March to April 2024 in Tanah Rata Village, Banda, using fish samples obtained from local fishers through a simple random sampling method. Collected data included total length, body weight, sex, and gonad weight, which were analyzed descriptively. The results showed that P. hamrur exhibited a negative allometric growth pattern, with b values of 1.6664 (females) and 0.9055 (males). The fish length ranged from 21 to 42.3 cm, with weights between 105 and 327 grams. The gonadal maturity stages (GMS) consisted of five reproductive development phases for both sexes. The gonadosomatic index varied from 0.075 to 2.382 in females and from 0.04 to 2.35 in males, with a tendency for GSI to increase with body size. Females generally showed higher GSI values than males, indicating a greater reproductive readiness. These findings provide important insights into the reproductive status and population dynamics of P. hamrur in Banda waters, serving as a basis for sustainable management and conservation of fishery resources.